ANALISIS PERPINDAHAN PANAS PADA KOLEKTOR PLAT DATAR SEBAGAI SUMBER ENERGI TERMAL PADA PENGERING TIPE RAK - Budiman Sudia; Lukas Kano Mangalla; Samhuddin Samhuddin; Wa Ode Zulkaidah (Dinamika : Jurnal Ilmiah Teknik Mesin, 2019)
Solar collectors are devices that convert solar radiation energy into thermal energy which is used for  various purposes. This study is used to determine the heat in the flat plate collector as a source of thermal energy. Data collection was carried out at Kambu, Kendari City with a latitude of 40 LS, in May 2018. The intensity of solar radiation measured  using solar power meter : collector temperature measured using a thermocouple type CC (Cooper Constanta), wind speed  measured using anemometer,  the ambient temperature uses a mercury air thermometer. The Results show that the maksimum useful energy was 100, 09 W (Qu.act) and 182,01 W (Qu.teo) ; maksimum efficiency was 36,54 (hact ) and 77,2 % (hteo).